Konstruksi Sosial dalam Tradisi Begawe pada Masyarakat Dusun Tibulilin Lombok Barat - Ubaidi, Muh. Izzat; Aziz, Fakhrudin (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
This study analyzes the tradition of working in Tibulilin Hamlet as a social construction that plays a role in strengthening social solidarity, forming collective identity, and strengthening community social capital. Begawe is a tradition of mutual cooperation in organizing family events or large celebrations, where all members of the community are actively involved. Using a qualitative approach based on participatory observation, this study draws on Emile Durkheim's theory of Structural Functionalism and Pierre Bourdieu's concept of social capital. The results of the study show that begawe is not only a cultural ritual, but also a means of strengthening social relations through mechanical solidarity, reflected in cross-individual cooperation regardless of differences. Cultural elements such as traditional clothing and special foods act as symbols of collective identity that reinforce a shared awareness of local values. The practice of mutual cooperation during work strengthens social networks, creates mutual trust, and maintains social stability. These findings show that the tradition of begawe remains relevant in the midst of the challenges of modernization, playing a role as a form of social harmony that survives and develops in the era of globalization.